Trends of Candida species causing bloodstream infections in South-Eastern Asia: A systematic review and meta-analysis - Dina Yamin; Abubakar Muhammad Wakil; Mohammed Dauda Goni; Ahmad Adebayo Irekeola; Khalid Hajissa (Asian Pacific Journal of Tropical Medicine)
A reliable estimation of Candida bloodstream infection prevalence is increasingly important to track changes in Candida species distribution and define burden of ongoing candidemia. A systematic review and meta-analysis were conducted to estimate candidemia prevalence and identify patterns of Candida species in South-eastern Asia. Systematic electronic-databases literature search was performed on published studies recorded candidemia prevalence in South-Eastern Asia. Using meta-analysis of proportions, the overall pooled prevalences of candidemia by Candida (C.) albicans, C. tropicalis, C. parapsilosis and C. glabrata were calculated as 28.4% (95% CI 24.9-31.8), 29.2% (95% CI 24.7-33.7), 19.1% (95% CI 14.8-23.4) and 14.0% (95% CI 10.4-17.5), respectively. Based on publication year and country, subgroup analyses were conducted on Candida species to determine heterogeneity source. The findings may not precisely reflect true candidemia prevalence in different countries. Therefore, it highlights continuous need to conduct prevalence studies, assess and monitor growing burden, control effect of potential risk factors and implement regional surveillance programs to prevent further rise.